Effect of nutrient deprivation on lipid yield of scenedesmus dimorhus - Kathy, Dang (Universiti Malaysia Sarawak (UNIMAS), 2011)
Scenedesmus dimorphus is a four-celled colony algae. It was speculated that the species have 16-40% of lipid yield. The environmental stressor especially under nitrogen limitation could enhance lipid accumulation. In the current study, the species was cultivated in different nitrogen concentration at pH 5, 7 and 9. The growth was compared. The outdoor cultivation was carried out at nutrient sufficient and nutrient deficiency conditions. The algal biomass was harvested at 16th days of cultivation for nutrient deficiency experiment and 18th days from that of nutrient sufficient. The lipid was extracted from algal biomass using Soxhlet method with n-hexane. Results showed that Scenedesmus dimorphus had optimum growth at higher nitrogen concentration at neutral pH while optimum growth occurred at low nitrogen concentration under pH 5 and 9. The lipid yield produced in N-sufficient cultivation was about 2.09% while the lipid yield produced in from N-starved cultivation was about 2.33%. The lipid content was not affected by the nitrogen limitation in the culture.